2021
DOI: 10.3390/horticulturae7120563
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 Nanoparticles on the Yield and Photophysiological Responses of Cherry Tomatoes during the Rainy Season

Abstract: The rainy season occurs mainly from June to July in Korea, and this season causes insufficient ambient light intensity for the growth of cherry tomato in a greenhouse. Titanium dioxide (TiO2), as a photocatalyst, is known to affect photosynthesis in plants. This study was carried out to investigate the influence of TiO2 foliar spray application on the yield and photophysiological responses of cherry tomato under low ambient light intensity during the rainy season in a greenhouse. Cherry tomato plants were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…At 75 µmol m −2 s −1 PPFD during cultivation, TiO 2 nanoparticle spray (100 μmol L −1 ) tended to sustain higher Φ PSII and rETR values. In accordance, it has been shown that foliar spraying of 100 mg L −1 of TiO 2 nanoparticles under low light intensity increased the rate of photosynthesis and yield in cherry tomato plants 30 .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…At 75 µmol m −2 s −1 PPFD during cultivation, TiO 2 nanoparticle spray (100 μmol L −1 ) tended to sustain higher Φ PSII and rETR values. In accordance, it has been shown that foliar spraying of 100 mg L −1 of TiO 2 nanoparticles under low light intensity increased the rate of photosynthesis and yield in cherry tomato plants 30 .…”
Section: Discussionmentioning
confidence: 54%
“…In the study of Hossein et al 29 , foliar application of 2.5 mg L −1 Ti, chlorophyll pigments (chlorophyll a, b, carotenoid), plant biomass, photochemical efficiency of photosystem II (F v /F m ) and electron transfer rate (ETR) of soybean improve under natural light conditions. Choi et al 30 reported that TiO 2 foliar application affected CO 2 absorption and chlorophyll fluorescence of cherry tomato plants. Foliar spraying of TiO 2 during cloudy days with low light intensity increased the electron transfer rate from Q A to Q B in the reaction center of photosystem II (ET 0 /RC) and carbon dioxide (CO 2 ) stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…There are various studies that have shown increases in the yield of tomato plants after TiO2 treatment. For instance, the yield of tomato plants was reported to increase after 100 mg L -1 by foliar spray application (Choi, 2021). In another study, the positive effect of TiO2 treatment on the yield of tomato plant by foliar application was reported (Parveen and Siddique, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…The ChlF induction curve with fast chlorophyll fluorescence induction curve (O-J-I-P) steps obtained from different plants can show a significant change under nanoparticles treatment [ 32 , 60 ]. The mechanisms underlying the regulation of photosynthesis by nanoparticles are related to decreasing or enhancing the chlorophyll content and electron transport rate, influencing the performance of PSII, and CO 2 assimilation, causing damages to chloroplast components, broadening the chloroplast photoabsorption spectrum, regulating Hill reaction and Calvin cycle, changing the activity of key photosynthetic enzymes like Rubisco, moreover, light harvesting NPs (e.g.…”
Section: Discussionmentioning
confidence: 99%